Modulating Biochar Properties Through Pyrolysis Temperature for Different Applications - Martina Fazi; Domenico Rosa; Luca Di Palma (Chemical Engineering Transactions)
Biochar, the solid product of biomass carbonization, is a versatile material that can be used for different applications. This material is a sustainable solution for many environment issues, like food waste treatment, greenhouse gases emission reduction and soil remediation. In this work, slow pyrolysis was used to produce biochar from agri-food waste at three different temperatures (500, 800 and 900 °C) for 1 hour as residence time. The produced biochars were characterized through SEM and EDS analisys. Point of zero charge (pHZC) was measured, and the leaching of nutrients and anions from biochars was investigated. Results show that biochar main characteritics strongly depended on the sinthesys temperature: at increasing pyrolysis temperature point of zero charge increased, as well as the leaching of chlorides phosphates and nitrates. Adsorption tests were then carried out to assess the adsorption properties of biochars synthesized at different temperatures. The biochar produced at 500 °C proved to be the most effective in the removal of organic dyes in water. According to the results of the characterization study, some applications were proposed for the synthetized biochars.